Sodium salt composition, sodium ion battery electrolyte and application thereof, and sodium ion battery
By using a variety of sodium ion battery electrolyte prepared with a variety of sodium salt compositions, a multipole solvated shell layer and an inorganic-rich electrolyte interface film are formed, which solves the problem of instability of the sodium ion battery electrode/electrolyte interface, and significantly improves the cycle stability and rate performance of the battery.
Patent Information
- Application Number
- CN202411822893.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The high degree of instability of the electrode/electrolyte interface during the cycle of sodium ion batteries leads to continuous electrolyte side reactions, transition metal leaching and rapid capacity attenuation, reducing the cycle stability and rate performance of sodium ion batteries.
An aggregate electrolyte with a multipole solvated shell layer is prepared by using any five or more of sodium bistrifluoromethanesulfonimide, sodium hexafluorophosphate, sodium difluorooxalic acid borate, sodium fluoroborate, sodium nitrate, sodium perchlorate and sodium difluorophosphate, to form a solid electrolyte interface film on the surface of the positive electrode and the negative electrode rich in inorganic substances to effectively protect the electrode.
By forming a stable solid electrolyte interface mask, the cycle stability and rate performance of sodium ion batteries are improved, extending the battery life and reducing costs.
Smart Images

Figure CN119542547A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium salt composition, a sodium ion battery electrolyte and application thereof, and a sodium ion battery. Background Art
[0002] With the continuous development of human society, how to develop and utilize energy efficiently and safely has become a major challenge for mankind. The utilization of clean energy such as solar energy, wind energy and tidal energy requires the development of large-scale energy storage technology. Lithium-ion batteries are currently the preferred energy storage devices in portable electronic devices and electric vehicles due to their advantages such as high energy density, low self-discharge and long cycle life. However, in the application of large-scale energy storage, lithium-ion batteries still face the problem of scarce lithium resources. Sodium-ion batteries and lithium-ion batteries have similar working principles, and the sodium resources on the earth are very abundant. At the same time, sodium-ion batteries also have the advantages of low cost and good cycle life. They are strong competitors in the field of large-scale energy storage. However, the high instability of the electrode / electrolyte interface during the cycle process has seriously hindered the development of sodium-ion batteries. In particular, the unstable cathode electrolyte interface (CEI) will lead to continuous electrolyte side reactions, transition metal leaching and rapid capacity decay, thereby reducing the cycle stability and rate performance of sodium-ion batteries. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a sodium salt composition, a sodium ion battery electrolyte and its application, and a sodium ion battery. The electrolyte prepared by the sodium salt composition is an aggregate with a multipolar solvation shell, which can form a positive electrode surface solid electrolyte interface film (CEI) rich in inorganic substances and a negative electrode surface solid electrolyte interface film (SEI), effectively protecting the positive electrode and the negative electrode, and improving the cycle stability and rate performance of the sodium ion battery.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The invention provides a sodium salt composition, comprising any five or more of sodium bis(trifluoromethanesulfonyl)imide, sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium fluoroborate, sodium nitrate, sodium perchlorate and sodium difluorophosphate.
[0006] Preferably, the amounts of the various sodium salts in the sodium salt composition are the same.
[0007] The present invention also provides a sodium ion battery electrolyte, comprising a sodium salt composition, an organic solvent and an additive;
[0008] The sodium salt composition is the sodium salt composition described in the above technical solution;
[0009] The solvation configuration of the sodium ion battery electrolyte is an aggregate with multipolar solvation shells;
[0010] The concentration of the sodium salt composition in the sodium ion battery electrolyte is 0.5 to 0.8 mol / L;
[0011] The volume percentage of the aggregate in the sodium ion battery electrolyte is 70-85%.
[0012] Preferably, the organic solvent includes one or more of tetrahydrofuran, ethylene glycol dimethyl ether and dioxolane.
[0013] Preferably, the additive includes one or more of ethylene carbonate, vinylene carbonate, propylene sulfite and vinyl sulfate.
[0014] Preferably, the mass concentration of the additive in the sodium ion battery electrolyte is 3-5%.
[0015] The present invention also provides the use of the sodium ion battery electrolyte described in the above technical solution in a sodium ion battery.
[0016] The present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is the sodium ion battery electrolyte described in the above technical solution.
[0017] Preferably, the active material of the positive electrode includes layered oxides, Prussian blue compounds or polyanionic compounds.
[0018] Preferably, the negative electrode comprises hard carbon, sodium metal or sodium titanium phosphate.
[0019] The present invention provides a sodium salt composition, including any five or more of sodium bis(trifluoromethanesulfonyl)imide, sodium hexafluorophosphate, sodium difluorooxalate borate, sodium fluoroborate, sodium nitrate, sodium perchlorate and sodium difluorophosphate. In an electrolyte, organic solvent molecules are arranged around sodium ions to form a solvation shell. The solubility of each sodium salt in the sodium salt composition provided by the present invention is different, and the difficulty of dissociation in an organic solvent is also different. The addition of sodium salts with low solubility and strong coordination ability (such as NaNO3, NaBF4) can change the solvent shell structure. Under the effect of a variety of sodium salts, sodium salts with strong coordination with organic solvents (such as NaNO3, NaBF4) will enter the first solvation shell (the first layer of solvent molecules formed by organic solvent molecules around sodium ions) to increase the negative charge around the sodium ions, drive other more sodium ions to approach each other, and the aggregation of multiple sodium ions can cause the local concentration in the electrolyte to increase. As the distance from the sodium ion core increases, the arrangement of organic solvent molecules becomes less tight, forming the second and third solvation shells, which results in the aggregation of multiple solvation shells to form a large aggregate. This multipolar solvation structure, which is regulated by the solubility of different sodium salts, allows a variety of anions to form in a random combination (e.g., 2 TFSI - +1 BF4 - +1 DFOB - Or 1 NO3 - +1 TFSI - +1 PF6 - +1 BF4 - , generally 4 in total) enter the first solvation shell, various anions migrate with the sodium ions during the charge and discharge process, and the sodium ions are desolvated when they are close to the positive and negative electrode interfaces. In the multi-anion solvent shell, due to the different bond energies between different anions and sodium ions, the desolvation energy of sodium ions can be effectively reduced in this disordered state, thereby improving the reaction kinetics of the positive and negative electrode interfaces. The anions then undergo redox reactions at the positive and negative electrode interfaces to form inorganic substances rich in F, S, B, N, and P (such as NaF, Na3N, SO3 - PO2 - , BO -) on the positive electrode surface solid electrolyte interface film (CEI) and the negative electrode surface solid electrolyte interface film (SEI), which effectively protects the positive and negative electrodes, thereby improving the cycle stability and rate performance of sodium ion batteries. The participation of multiple anion groups in the electrolyte leads to a greater diversity of solvation structures. The participation of anions weakens the interaction between sodium ions and solvent molecules, promotes sodium ion diffusion and the formation of stable interphase passivation layers (CEI, SEI). Compared with single-salt electrolytes, low-concentration electrolytes with multiple sodium salts show enhanced cycle stability and rate performance.
[0020] The results of the embodiment show that when NaNi 1 / 3 Mn 1 / 3 Fe 1 / 3 The button cell with O2 positive electrode has an excellent capacity retention rate of 89.48% at a cut-off voltage of 4V and 0.5C (1C = 120mAh / g) for 250 cycles, and also has good cycle performance under low and high temperature conditions. The present invention provides valuable insights into the application of high entropy and low concentration electrolytes in sodium ion batteries.
[0021] In addition, the cost of sodium salt is usually more than ten times that of solvent. The cycle stability and rate performance of the sodium ion battery electrolyte provided by the present invention are higher than those of the single salt electrolyte with the same sodium salt concentration. Therefore, under the requirements of the same cycle stability and rate performance, the sodium salt concentration in the sodium ion battery electrolyte provided by the present invention is low, and the use of sodium salt can be reduced, which can effectively reduce the cost of sodium ion batteries, thereby facilitating the large-scale application of sodium ion batteries in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Graphs showing radial distribution function (solid line) and coordination number (dashed line) calculated by molecular dynamics (MD) simulation of the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1, where a is NTF and b is HEE electrolyte;
[0023] Figure 2 It is a simulation diagram of the solvation structure of the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1;
[0024] Figure 3 It is a pie chart of the solvation configuration distribution in the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1;
[0025] Figure 4 The wave number range is 550 to 1000 cm -1 The Raman spectra of the single salt electrolyte (NTF) of Comparative Example 1, the HEE electrolyte of Example 1 and tetrahydrofuran (THF) (e) and the Na NMR spectrum of 23Na+ Coordination environment diagram (f);
[0026] Figure 5 The anions, solvent and Na in the HEE electrolyte prepared in Example 1 + Binding energy diagram of
[0027] Figure 6 The calculated HOMO energy level diagram of anion molecules and solvent in the HEE electrolyte prepared in Example 1;
[0028] Figure 7 Aurbach Coulomb efficiency diagram (a) of Na||Cu battery assembled with single salt electrolyte (NTF) of Comparative Example 1 and HEE electrolyte of Example 1 and LSV curve diagram (b) of Na||stainless steel half-cell;
[0029] Figure 8 The Tafel curve and exchange current density (i0) diagram (c) of the Na||Na battery assembled with the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 at high overpotential, and the Nyquist diagram (d) of the Na||Na battery at NTF from 303 to 343K;
[0030] Fig. 9 Nyquist plot (e) of the Na||Na battery in the HEE electrolyte of Example 1 from 303 to 343 K and the Na of the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 + Desolvation energy diagram (f);
[0031] Fig.10 The cycle performance diagram (a) of the Na||NaNMF battery assembled using the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 in the voltage range of 2-4V at 0.5C and the cycle performance diagram (b) in the voltage range of 2-4.1V at 0.33C;
[0032] Fig.11 The Na||NaNMF battery assembled with the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 at 18 mg·cm -2 The cycling performance of the positive electrode (c) and the low temperature (-20°C) performance of the two electrolytes (d);
[0033] Fig.12 The high temperature (40°C) performance graph (e) and the rate performance graph (f) of the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1;
[0034] Fig.13TOF-SIMS 3D analysis (a) and TOF-SIMS 2D surface mapping (b) of secondary ion fragments on the NaNMF cathode after cycling using the HEE electrolyte of Example 1;
[0035] Fig.14 (c) and (d) are the XPS spectra of C1s and F1s on the NaNMF positive electrode after cycling using the HEE electrolyte of Example 1;
[0036] Fig.15 (e) XPS spectra of P 2p and (f) XPS spectra of S2p on the NaNMF positive electrode after cycling using the HEE electrolyte of Example 1;
[0037] Fig.16 The XPS spectra of N1s (g) and B1s (h) on the NaNMF positive electrode after cycling using the HEE electrolyte of Example 1;
[0038] Fig.17 DRT calculation and charge / discharge curves of the in-situ EIS of the Na||NaNMF battery assembled with the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 at the 1st and 20th cycles, where a is the 1st cycle of the single salt electrolyte, b is the 1st cycle of the HEE electrolyte, c is the 20th cycle of the single salt electrolyte, and d is the 20th cycle of the HEE electrolyte;
[0039] Fig.18 GITT charge-discharge voltage curves (e) of the Na||NaNMF battery assembled with the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 after 50 cycles and the corresponding DNa of the NaNMF positive electrode + Figure (f);
[0040] Fig.19 NaNi prepared in Application Example 1 1 / 3 Mn 1 / 3 Fe 1 / 3 Characterization diagram of O2(NaNMF), where af is the element distribution diagram of SEM, g is the SEM morphology diagram, and h is the XRD diagram. DETAILED DESCRIPTION
[0041] The invention provides a sodium salt composition, comprising any five or more of sodium bis(trifluoromethanesulfonyl)imide, sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium fluoroborate, sodium nitrate, sodium perchlorate and sodium difluorophosphate.
[0042] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0043] As an embodiment, the sodium salt includes any five or more of sodium bistrifluoromethanesulfonimide (NaTFSI), sodium hexafluorophosphate (NaPF6), sodium difluorooxalatoborate (NaDFOB), sodium fluoroborate (NaBF4), sodium nitrate (NaNO3), sodium perchlorate (NaClO4) and sodium difluorophosphate (NaDFP), and in specific embodiments, they are NaTFSI, NaPF6, NaDFOB, NaBF4 and NaNO3, or NaTFSI, NaClO4, NaDFOB, NaBF4 and NaNO3, or NaDFP, NaClO4, NaDFOB, NaBF4 and NaNO3.
[0044] As an embodiment, the amount of each sodium salt in the sodium salt composition is the same.
[0045] The present invention also provides a sodium ion battery electrolyte, comprising a sodium salt composition, an organic solvent and an additive;
[0046] The sodium salt composition is the sodium salt composition described in the above technical solution;
[0047] The solvation configuration of the sodium ion battery electrolyte is an aggregate with multipolar solvation shells;
[0048] The concentration of the sodium salt composition in the sodium ion battery electrolyte is 0.5 to 0.8 mol / L;
[0049] The volume percentage of the aggregate in the sodium ion battery electrolyte is 70-85%.
[0050] As an embodiment, the organic solvent includes one or more of tetrahydrofuran, ethylene glycol dimethyl ether and dioxolane, and in a specific embodiment, tetrahydrofuran.
[0051] As an embodiment, the additive includes one or more of ethylene carbonate, vinylene carbonate, propylene sulfite and vinyl sulfate, and in a specific embodiment, ethylene carbonate. The main function of the additive in the present invention is to form a stable SEI on the surface of the negative electrode and enhance the mechanical strength of the SEI.
[0052] As an embodiment, the concentration of the sodium salt composition in the sodium ion battery electrolyte is 0.5 to 0.6 mol / L.
[0053] In an embodiment of the present invention, the concentration of the sodium salt composition in the sodium ion battery electrolyte is 0.5 mol / L, and the sodium salt composition is NaTFSI, NaPF6, NaDFOB, NaBF4 and NaNO3, wherein the concentration of each sodium salt is 0.1 mol / L.
[0054] As an embodiment, the volume percentage of the aggregate in the sodium ion battery electrolyte is 75-80%.
[0055] As an implementation mode, the mass concentration of the additive in the sodium ion battery electrolyte is 3-5%, and in a specific embodiment is 5%.
[0056] The electrolyte solvation structure refers to the interaction and arrangement between the solvent molecules and the solute molecules in the electrolyte. This structure has an important influence on the electrochemical properties of the electrolyte, including the charge and discharge efficiency and cycle stability of the battery.
[0057] In the electrolyte, organic solvent molecules are arranged around sodium ions to form a solvation shell. The solubility of each sodium salt in the sodium salt composition provided by the present invention is different, and the difficulty of dissociation in the organic solvent is also different. The addition of sodium salts with low solubility and strong coordination ability (such as NaNO3, NaBF4) will change the solvent shell structure. Under the effect of multiple sodium salts, sodium salts with strong coordination with organic solvents (such as NaNO3, NaBF4) will enter the first solvation shell (the first layer of tightly arranged solvent molecules formed by organic solvent molecules around sodium ions), which will increase the negative charge around the sodium ions, drive more other sodium ions to approach each other, and the aggregation of multiple sodium ions will cause the local concentration in the electrolyte to increase. As the distance from the sodium ion core becomes farther and farther, the arrangement of organic solvent molecules will become less tight, forming a second layer, a third layer, etc., so as to produce the aggregation of multiple solvation shells and form a large aggregate. This multipolar solvation structure regulated by the solubility of different sodium salts allows a variety of anions to be randomly combined (such as 2 TFSI - +1 BF4 - +1 DFOB - Or 1 NO3 - +1 TFSI - +1 PF 6- +1 BF 4-, generally 4 in total) enter the first solvation shell, various anions migrate with sodium ions during the charge and discharge process, and sodium ions are desolvated when they are close to the positive electrode interface and the negative electrode interface. In the multi-anion solvent shell, due to the different bond energies between different anions and sodium ions, the desolvation energy of sodium ions can be effectively reduced in this disordered state, thereby improving the reaction kinetics of the positive electrode interface and the negative electrode interface. The anions thus undergo redox reactions at the positive electrode interface and the negative electrode interface to form a positive electrode surface solid electrolyte interface film (CEI) and a negative electrode surface solid electrolyte interface film (SEI) rich in inorganic substances, which effectively protects the positive and negative electrodes, thereby improving the cycle stability and rate performance of sodium ion batteries. The participation of multiple anion groups in the electrolyte leads to greater diversity of solvation structures. The participation of anions reduces the interaction between sodium ions and solvent molecules, and promotes the diffusion of sodium ions and the formation of stable interphase passivation layers (CEI, SEI). Compared with single-salt electrolytes, low-concentration electrolytes with multiple sodium salts show enhanced cycling stability and rate performance.
[0058] The solid electrolyte interface (CEI) film on the cathode surface is beneficial to Na + The diffused organic derivatives are located in the outer layer, which is beneficial to Na + The diffusion of CEI ensures its toughness. The inorganic substances with strong mechanical strength serve as pillars to effectively protect the integrity of the positive electrode particles. The various components are evenly coordinated to form a stable CEI. The dense and uniform CEI is conducive to the charge transfer of the interface, thus achieving long-term cycle performance.
[0059] In addition, the cost of sodium salt is usually more than ten times that of solvent. The cycle stability and rate performance of the sodium ion battery electrolyte provided by the present invention are higher than those of the single salt electrolyte with the same sodium salt concentration. Therefore, under the requirements of the same cycle stability and rate performance, the sodium salt concentration in the sodium ion battery electrolyte provided by the present invention is low, and the use of sodium salt can be reduced, which can effectively reduce the cost of sodium ion batteries, thereby facilitating the large-scale application of sodium ion batteries in the field of energy storage.
[0060] As an embodiment, the method for preparing the sodium ion battery electrolyte comprises the following steps:
[0061] In an inert atmosphere, a sodium salt is dissolved in a mixed solution of an organic solvent and an additive to obtain the sodium ion battery electrolyte.
[0062] As an embodiment, the inert atmosphere is argon.
[0063] Before the dissolution, the present invention further comprises: drying the sodium salt in an inert atmosphere or in a vacuum; the inert atmosphere is argon; the vacuum degree of the vacuum is 25 kPa; the drying temperature is 80 to 100° C., and in a specific embodiment, it is 80 to 90° C.; the drying time is 5 to 12 hours, and in a specific embodiment, it is 12 hours.
[0064] Before the dissolution, the present invention further comprises: subjecting the organic solvent and the additive to molecular sieve drying treatment and filtering; the pore size of the molecular sieve used in the molecular sieve drying treatment is The molecular sieve drying treatment time is 5 to 12 hours, and in a specific embodiment is 10 to 12 hours; the pore size of the sieve used for the filtration is 0.22 μm.
[0065] The present invention has no particular limitation on the dissolution process, and any dissolution process known in the art may be used.
[0066] The present invention also provides the use of the sodium ion battery electrolyte described in the above technical solution or the sodium ion battery electrolyte prepared by the preparation method described in the above technical solution in a sodium ion battery.
[0067] The present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte of the sodium ion battery is the sodium ion battery electrolyte described in the above technical solution or the sodium ion battery electrolyte prepared by the preparation method described in the above technical solution.
[0068] As an embodiment, the active material of the positive electrode includes layered oxides, Prussian blue compounds or polyanionic compounds, and in a specific embodiment, layered oxides.
[0069] As an embodiment, the layered oxide includes sodium nickel manganese ferrite, specifically NaNi 1 / 3 Mn 1 / 3Fe 1 / 3 O2; the polyanionic compound includes sodium vanadium phosphate (Na3V2(PO4)3) or sodium vanadium fluorophosphate (Na3V2(PO4)2F3); the Prussian blue compound is Na2Mn[Fe(CN)6].
[0070] As an embodiment, the NaNi 1 / 3 Mn 1 / 3 Fe 1 / 3 The preparation method of O2 comprises the following steps: mixing Na2CO3, NiO, Mn2O3 and Fe2O3, ball milling, drying and crushing, calcining the obtained powder, and obtaining NaNi 1 / 3 Mn 1 / 3Fe 1 / 3 O2.
[0071] As an embodiment, the Na2CO3, NiO, Mn2O3 and Fe2O3 are all purchased from Aladdin; the purity of the Na2CO3 is 99.9%; the purity of the NiO is 99%; the purity of the Mn2O3 is 98%; the purity of the Fe2O3 is 99%; the molar ratio of Na in the Na2CO3, Ni in the NiO, Mn in the Mn2O3 and Fe in the Fe2O3 is 1:1 / 3:1 / 3:1 / 3; the equipment used for the ball milling is a planetary ball mill (MITR ZQM-2L / 4L); the rotation speed of the ball mill is 200-300rpm, and is 300rpm in the specific embodiment; the ball milling time is 5-10h, and is 10h in the specific embodiment; the ball milling uses anhydrous ethanol as a medium; the mass ratio of solid material to medium in the ball milling process is 1:5; the drying temperature is 50-70°C, and is 55-65°C in the specific embodiment; the drying time is 5-10h, and is 10h in the specific embodiment; the pulverization is grinding on a mortar; the particle size of the powder is 3-8μm, and is 5μm in the specific embodiment; the calcination temperature is 850-1000°C, and is 950°C in the specific embodiment; the calcination time is 10-15h, and is 14h in the specific embodiment; the calcination is carried out in air; after the calcination, it also includes: cooling the calcined product to 100°C, taking it out of the furnace and immediately transferring it to a glove box filled with argon, cooling it to room temperature and then storing it to avoid exposure to air.
[0072] As an embodiment, the negative electrode includes hard carbon, sodium metal or sodium titanium phosphate, and in a specific embodiment, sodium metal.
[0073] As an embodiment, the diaphragm includes glass fiber, polypropylene (PP) or polyethylene (PE), and in a specific embodiment, it is glass fiber.
[0074] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0075] Example 1
[0076] NaTFSI, NaPF6, NaDFOB, NaBF4, and NaNO3 were dried at 80°C for 12 h under 25 kPa vacuum and then used. Tetrahydrofuran (THF) and ethylene carbonate (FEC) were used After the molecular sieve is dried for 10 hours, impurities are filtered out with a filter with a pore size of 0.22 μm for later use; NaTFSI, NaPF6, NaDFOB, NaBF4, and NaNO3 are dissolved in a mixture of tetrahydrofuran (THF) and ethylene carbonate (FEC) to obtain a sodium ion battery electrolyte (HEE electrolyte), wherein the concentration of each sodium salt is 0.1 mol / L, totaling 0.5 mol / L, and the mass concentration of ethylene carbonate in the sodium ion battery electrolyte is 5%.
[0077] Example 2
[0078] The difference from Example 1 is that the five sodium salts in the sodium ion battery electrolyte (HEE electrolyte) are NaTFSI, NaClO4, NaDFOB, NaBF4, and NaNO3, respectively, and the concentration of each sodium salt is 0.1 mol / L, totaling 0.5 mol / L.
[0079] Example 3
[0080] The difference from Example 1 is that the five sodium salts in the sodium ion battery electrolyte (HEE electrolyte) are NaDFP, NaClO4, NaDFOB, NaBF4, and NaNO3, respectively, and the concentration of each sodium salt is 0.1 mol / L, totaling 0.5 mol / L.
[0081] Comparative Example 1
[0082] The difference from Example 1 is that the five sodium salts in Example 1 are replaced by NaTFSI to obtain a single-salt electrolyte NTF, wherein the concentration of NaTFSI is 0.5 mol / L.
[0083] Comparative Example 2
[0084] The difference from Example 1 is that the five sodium salts in Example 1 are replaced by NaPF6 to obtain a single-salt electrolyte NPF, in which the concentration of NaPF6 is 0.5 mol / L.
[0085] Application Example 1
[0086] NeNi 1 / 3 Mn 1 / 3 Fe 1 / 3Preparation of O2: A stoichiometric mixture of Na2CO3 (purity of 99.9%, Aladdin), NiO (purity of 99%, Aladdin), Mn2O3 (purity of 98%, Aladdin) and Fe2O3 (purity of 99%, Aladdin) (the molar ratio of Na:Ni:Mn:Fe is 1:1 / 3:1 / 3:1 / 3) was ball-milled in anhydrous ethanol at 300 rpm for 10 h in a planetary ball mill (MITRZQM-2L / 4L). The mass ratio of the solid material to anhydrous ethanol during the ball milling process was 1:5. The resulting mixture was dried at 65°C for 10 h and ground in a mortar to obtain a powder with a particle size of 5 μm, which was then calcined at 950°C in air for 14 h. At the end of the calcination, when the temperature dropped to 100°C, the sample was taken out of the furnace and immediately transferred to an argon-filled glove box to continue cooling to room temperature and stored;
[0087] The NaNi 1 / 3 Mn 1 / 3 Fe 1 / 3 O2 is the active material of the positive electrode, sodium metal is the negative electrode, glass fiber is the separator, and the HEE electrolyte of Example 1 is the electrolyte to assemble a Na||NaNMF battery;
[0088] A Na||Cu battery was assembled using Cu foil as the positive electrode, sodium metal as the negative electrode, glass fiber as the separator, and the HEE electrolyte of Example 1 as the electrolyte;
[0089] A Na|| stainless steel half-cell was assembled using a stainless steel gasket as a positive electrode, sodium metal as a negative electrode, glass fiber as a separator, and the HEE electrolyte of Example 1 as an electrolyte;
[0090] A Na||Na battery was assembled using sodium metal as a positive electrode, sodium metal as a negative electrode, glass fiber as a separator, and the HEE electrolyte of Example 1 as an electrolyte.
[0091] Comparative application example 1
[0092] The difference from Application Example 1 is that the HEE electrolyte in Example 1 is replaced by the single salt electrolyte NTF in Comparative Example 1.
[0093] Performance Testing
[0094] The morphology and microstructure of the samples were characterized by scanning electron microscopy (SEM, JSM 7800F, JEOL) and transmission electron microscopy (TEM, JEOL JEM-F200).
[0095] The chemical composition of the samples was determined by X-ray photoelectron spectroscopy (XPS, K-Alpha+, Thermo Fisher Scientific).
[0096] Raman spectra were recorded using a Renishaw inVia Raman microscope and λ=532 nm laser radiation.
[0097] A Rigaku Miniflex II XRD instrument with Cu Kα radiation was used. The crystallographic information of the synthesized products was examined by X-ray diffraction (XRD).
[0098] Standard inspections were performed at a scan rate of 5° per minute over a scanning angle range of 5° to 90°. 3D reconstruction images were obtained using time-of-flight secondary ion mass spectrometry (TOF-SIMS).
[0099] In situ electrochemical impedance spectroscopy (EIS) was performed on an electrochemical workstation (Solartron, USA) and a 2032 coin cell. The charge and discharge voltage range was 2–4 V and the rate was 0.2 C.
[0100] The frequency range of EIS test was 1,000,000-0.1 Hz and the amplitude was 10 mV. Before the in situ EIS test, the battery was run at a constant current density for different cycles.
[0101] The DRT transformation was performed using MATLAB software, and all parameters were kept consistent throughout the calculation process to ensure the consistency of the DRT results. The viscosity of the electrolyte was measured on a MSKSFM-VT viscometer at 28°C.
[0102] The 23Na-nuclear magnetic resonance (NMR) analysis of the electrolytes was performed using a Jeol ECZ500R 500MHz NMR spectrometer. Before the test, dimethyl sulfoxide (DMSO-d6) was mixed thoroughly with the electrolytes as a deuterated reagent.
[0103] (1) Figure 1 Graphs showing the radial distribution function (solid line) and coordination number (dashed line) calculated by molecular dynamics (MD) simulation of the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1, where a is NTF and b is HEE electrolyte.
[0104] The present invention conducts molecular dynamics (MD) simulation to confirm the solvation structure of HEE electrolyte and to clarify the difference in solvation structure with single salt electrolyte NTF. Figure 1 The radial distribution function shows that compared with the single-salt electrolyte NTF, although the concentration of each salt in the HEE electrolyte is lower, the anions of the five salts in the HEE electrolyte still enter the first solvation shell (dashed platform).
[0105] (2) Figure 2It is a simulation diagram of the solvation structure of the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1. Figure 3 It is a pie chart of the solvation configuration distribution in the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1.
[0106] Depend on Figure 2 and Figure 3 It can be seen that through the molecular simulation of the entire electrolyte, it is found that unlike the single salt electrolyte NTF, the anions in the HEE electrolyte aggregate to form multiple anions encapsulating Na + Clusters of Figure 1 The first platform of the dashed lines a and b corresponds to the coordination number. It can be found that the proportion of small aggregates (AGG) in the solvation configuration of the high-entropy electrolyte HEE is higher than that in the single-salt electrolyte NTF. The less AGG in NTF will lead to poor passivation of the organic-rich interface chemistry and electrochemical interface (CEI) derived from the single-salt electrolyte NTF, resulting in electrolyte consumption, low Coulomb efficiency (CE) and irreversible capacity loss. The high-entropy electrolyte HEE exhibits a salt-based solvation interaction, in which Na + The surrounding primary solvation shell is dominated by anions, resulting in an anion-derived inorganic-rich and robust CEI, passivating THF solvent co-intercalation and further electrolyte decomposition, thus enabling good cycling of the cathode.
[0107] (3) Figure 4 The wave number range is 550 to 1000 cm -1 The Raman spectra of the single salt electrolyte (NTF) of Comparative Example 1, the HEE electrolyte of Example 1 and tetrahydrofuran (THF) (e) and the Na NMR spectrum of 23Na + Coordination environment diagram (f).
[0108] Raman spectroscopy and nuclear magnetic resonance spectroscopy were used to further explore the coordination behavior of each component in the two electrolytes. Figure 4 As shown in Figure e, there is a peak associated with the main solvent tetrahydrofuran (THF) in both NTF and HEE electrolytes, which is around 860. The solvation intensity of 23Na liquid was studied by NMR spectroscopy, where the chemical shift reflects the effect of the solvation environment on Na + The solvation shell of high entropy electrolyte HEE and Na + The interaction between Figure 4 Compared with the displacement of the single-salt electrolyte NTF, it shows that the high electron density is generated due to the strong solvation interaction, Na + Subjected to more shielding, the state of anion aggregation in high-entropy electrolyte is demonstrated.
[0109] (4) Figure 5 The anions, solvent and Na in the HEE electrolyte prepared in Example 1 + Binding energy diagram. Figure 6 The calculated HOMO energy level diagram of anion molecules and solvent in the HEE electrolyte prepared in Example 1.
[0110] In order to explore the cause of anion aggregation in high entropy HEE electrolyte, Na + The AIMD simulations were performed using the Vienna Atomic Number Simulation Package (VASP.5.4.4) using the projector augmented wave (PAW) format. The Perdew-Burke-Ernzerhof (PBE) function was used to describe the exchange correlation energy. The long-range van der Waals (vdW) dispersion interaction was performed using the DFT-D3 method developed by Grimme and his collaborators. The plane wave energy cutoff was set to 400 eV, and the sampling point in the Brillouin zone was sampled only at the Γ point. The results are shown in Figure 2. Figure 5 As shown. Figure 5 It can be seen that Na + -NO3 - The binding energy of NaNO3 is the highest, indicating that NaNO3 is the most difficult to dissociate in the solvent. - There is a Na greater than 1 around the anion + Under the charge effect, it attracts other different anions to form multiple solvation shell aggregates. This solvation shell aggregate will cause multiple anions to follow the Na + They reach the cathode-electrolyte interface layer together and decompose to form CEI rich in various inorganic elements.
[0111] Depend on Figure 6 It can be seen that in the high entropy HEE electrolyte system, NO 3- and BF 4- It will first be oxidized and decomposed to form CEI rich in N, B, and F-derived inorganic substances.
[0112] (5) Figure 7 Aurbach Coulomb efficiency diagram (a) of the Na||Cu battery assembled with the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 and LSV curve diagram (b) of the Na||stainless steel half-cell. Figure 8 Tafel curves and exchange current density (i0) of the Na||Na battery assembled with the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 under high overpotential (c) and the Nyquist diagram of the Na||Na battery at NTF from 303 to 343K (d). Fig. 9Nyquist plot (e) of the Na||Na battery in the HEE electrolyte of Example 1 from 303 to 343 K and the Na of the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 + Desolvation energy diagram (f).
[0113] In order to study the reversibility of sodium metal deintercalation in different electrolytes, the Aurbach method was used to test the coulombic efficiency (CE) of the sodium / copper half-cell. The CE of the single salt electrolyte NTF and the high entropy electrolyte HEE were 93.84% and 97.71%, respectively. Figure 7 (a) This indicates that the high entropy electrolyte HEE has good reversibility of sodium metal deintercalation.
[0114] Furthermore, linear sweep voltammetry was performed at 1 mV·s -1 The oxidation stability of the two electrolytes was evaluated at a scan rate of Figure 7 (b), when the voltage exceeds 4.25 V, the oxidation current density of the single salt electrolyte NTF increases rapidly, indicating its weak oxidation stability. In contrast, the high entropy electrolyte HEE also maintains a lower current density at a voltage of 4.50 V, showing a wider electrochemical window. At the same time, at high overpotentials, the exchange current densities of NTF and HEE electrolytes are 4.28 and 5.25 mA cm, respectively. -2 ( Figure 8 c). Figure 8 Middle d, Fig. 9 Zhongehe Fig. 9 In Figure 5, electrochemical impedance spectroscopy (EIS) was used to evaluate the desolvation energy of the interface between two electrolytes in a symmetric Na||Na cell from 303 to 343 K. It can be calculated according to the Arrhenius equation:
[0115]
[0116] Where Rct, A, R, and T represent resistance, pre-exponential constant, standard gas constant, and absolute temperature, respectively. The activation energy is a function of temperature and Na + The resistance in HEE is determined by the resistance fitting during the desolvation process. + The desolvation energy is 58.4 kJ·mol -1 , which is significantly smaller than the desolvation energy in NTF (67.4 kJ·mol -1 The significant reduction in the energy barrier proves that the anion-enhanced solvation shell plays an important role in accelerating the Na + played a key role in the transmission.
[0117] (6) Fig.10The cycling performance diagram (a) and the cycling performance diagram (b) of the Na||NaNMF battery assembled using the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 in the voltage range of 2-4 V at 0.5C are shown in FIG.
[0118] Fig.11 The Na||NaNMF battery assembled with the single salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 at 18 mg·cm -2 The cycling performance diagram of the positive electrode (c) and the low temperature (-20℃) performance diagram of the two electrolytes (d).
[0119] Fig.12 The high temperature (40°C) performance diagram (e) and the rate performance diagram (f) of the single salt electrolyte (NTF) of comparative example 1 and the HEE electrolyte of example 1 are shown.
[0120] Adopts widely used O3 type NaNi 1 / 3 Mn 1 / 3 Fe 1 / 3 O2 is demonstrated as a positive electrode material. O3-type NaNi 1 / 3Mn 1 / 3 Fe 1 / 3 O2 materials have advantages in the cathode market due to their simple synthesis route, high capacity and low cost. The electrochemical performance of the two electrolytes was tested in Na||NaNMF batteries. The high entropy electrolyte HEE has an excellent capacity retention rate of 89.48% after 250 cycles at a voltage range of 2-4V and a rate of 0.5C, which is better than the single salt electrolyte NTF ( Fig.10 At the same time, when the cut-off voltage is increased to 4.1V ( Fig.10 In (b), after 150 cycles, the capacity retention rate of the high entropy electrolyte HEE is 88.36%, which is much better than the single salt electrolyte NTF (56.32%).
[0121] In order to verify its practical application value, the surface capacity of the positive electrode was increased (18 mg cm -2 ), two electrolytes, single salt electrolyte (NTF) and HEE electrolyte, were tested. Fig.11 As shown in Figure c, the high entropy electrolyte HEE still maintains 88.94% of its capacity after 100 cycles, while the capacity of the single salt electrolyte NTF decays dramatically. The high entropy electrolyte HEE also has excellent performance under high and low temperature conditions, such as Fig.11 Medium D and Fig.12As shown in Figure e, at -20°C, the high entropy electrolyte HEE has a capacity retention rate of 83.84% after 200 cycles. In addition, it also has good performance at a high temperature of 40°C. Through the rate test of the two electrolytes, it can be seen that the high entropy electrolyte HEE also has good rate performance compared to the single salt electrolyte NTF ( Fig.12 (f)
[0122] (7) Fig.13 TOF-SIMS 3D analysis (a) and TOF-SIMS 2D surface mapping (b) of secondary ion fragments on the NaNMF positive electrode after cycling using the HEE electrolyte of Example 1.
[0123] Fig.14 (c) and (d) are the XPS spectra of C1s and F1s on the NaNMF positive electrode after cycling using the HEE electrolyte of Example 1.
[0124] Fig.15 (e) and (f) are the XPS spectra of P 2p and S 2p on the NaNMF positive electrode after cycling using the HEE electrolyte of Example 1.
[0125] Fig.16 (g) and (h) are the XPS spectra of N1s and B1s on the NaNMF positive electrode after cycling using the HEE electrolyte of Example 1.
[0126] In order to further study the distribution of CEI interface components on NaNMF, time-of-flight secondary ion mass spectrometry (TOF-SIMS) depth analysis was used. The TOF-SIMS depth distribution (normalized to the maximum value) of high entropy electrolyte HEE on the NaNMF cathode surface for 20 cycles was obtained, revealing the various components in the deep distribution of CEI. Fig.13 A and Fig.13 As shown in b, TOF-SIMS analysis shows that the high entropy electrolyte HEE forms inorganic substances rich in F, S, B, N, and P (such as NaF, Na3N, SO 3- ,PO 2- , BO - ) and the distribution of various components is relatively uniform.
[0127] In addition, X-ray photoelectron spectroscopy (XPS) was used to determine the composition of CEI on the surface of NaNMF cathode after cycling with high entropy electrolyte ( Figures 14 to 16 ). Through the C1s spectra before and after etching ( Fig.14As can be seen from c), the CEI formed by the high-entropy electrolyte HEE has a uniform composition and changes little before and after etching. From the F1s spectrogram ( Fig.14 d), it can be seen that the content of NaF increases after etching for 30 s, indicating that various anions decompose first at the initial stage of CEI formation, forming a CEI rich in NaF inside. At the same time, by observing the S2p spectrogram ( Fig.15 f), the peak of S-N appears after etching for 30 s, which can also indicate the preferential decomposition of TFSI - at the positive electrode interface, which is beneficial to the formation of a stable CEI. Through the analysis of the spectrograms of other inorganic elements, it can be found that the content of inorganic substances rich in F, S, B, N, and P (such as NaF, Na3N, SO3 - , PO2 - , BO - ) increases after etching in P 2p ( Fig.15 e), N 1s ( Fig.16 g), and B1s ( Fig.16 h), which further confirms that the inorganic elements inside the CEI are relatively rich. In summary, it can be concluded that the CEI structure formed by the high-entropy electrolyte HEE is as follows: organic derivatives that are beneficial to the diffusion of Na + are located on the outer layer, which is beneficial to the diffusion of Na + and ensures the toughness of the CEI. Inorganic substances rich in strong mechanical strength act as pillars, effectively protecting the integrity of the positive electrode particles. Each component is evenly coordinated to form a stable CEI, thereby achieving long-term cycling performance.
[0128] (8) Fig.17 Figure (8) shows the DRT calculation and charge / discharge curves of in-situ EIS for the Na||NaNMF battery assembled with the single-salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 at the 1st and 20th cycles, where a is the 1st cycle of the single-salt electrolyte, b is the 1st cycle of the HEE electrolyte, c is the 20th cycle of the single-salt electrolyte, and d is the 20th cycle of the HEE electrolyte.
[0129] Fig.18 Figure (9) shows the charge / discharge voltage curves (e) measured by GITT and the corresponding DNa of the NaNMF positive electrode (f) for the Na||NaNMF battery assembled with the single-salt electrolyte (NTF) of Comparative Example 1 and the HEE electrolyte of Example 1 after 50 cycles. + Figure (f).
[0130] In order to analyze the complex electrode-electrolyte interface evolution during charge and discharge, in-situ electrochemical impedance spectroscopy (in-situ EIS) analysis was carried out ( Fig.17ad), and further explore this issue through the distribution of relaxation time (DRT). DRT is a model-free method that can separate the complex and highly overlapping physical and chemical processes of electrochemical systems by converting EIS from frequency to time constant. It can be clearly seen that the medium and low frequency semicircles in the in situ EIS spectrum show dynamic evolution during the charge and discharge process, which can be attributed to the continuous reaction and phase change evolution of the cathode with the electrolyte during the charge and discharge process. Three different specific relaxation times can be distinguished in the DRT results, which are between 10-4 and 10-3, 10-1 to 1, and 10 to 102, and are marked as τ1, τ2, and τ3. The peak area of DRT represents the impedance value in a specific electrochemical process. The high frequency τ1 and the medium frequency τ2 symbolize the different interface transition responses and charge transfer evolution during the formation of CEI of NaNMF electrode, respectively. The right shift of the τ1 peak during the charge and discharge process indicates the continuous reaction between the cathode and the electrolyte, representing the irreversible process of CEI formation. τ2 represents the electrochemical kinetics related to charge transfer at the electrode-electrolyte interface. τ3 represents the mass transfer of the electrolyte in the pores at the electrode, which will not be analyzed here. First, from the DRT result τ1, the single-salt electrolyte NTF has a strong signal in the first cycle of charge and discharge, indicating that a strong reaction occurred at the interface; while in the high-entropy electrolyte HEE, the τ1 signal during the first cycle of charge and discharge is lower, indicating that the reaction at the interface is relatively stable. During the 20th cycle of charge and discharge, the high-entropy electrolyte has a stronger signal at τ1, indicating that it has formed a stable and dense CEI after the cycle, which effectively ensures the stability of the cycle. Secondly, at τ2, in the single-salt electrolyte NTF, its peak value increases during the cycle. In contrast, the high-entropy electrolyte HEE tends to be stable, indicating that the dense and uniform CEI is conducive to charge transfer at the interface. Constant current intermittent titration (GITT) and calculated sodium ion diffusion coefficient (DNa + ) The results show that the DNa of the positive electrode cycled in NaTFSI / SUL:OTE:FEC + Significantly higher ( Fig.18 (e, f), confirming the fast interfacial diffusion kinetics and strong structural stability during the charging and discharging process of high entropy electrolyte HEE.
[0131] (9) Fig.19 NaNi prepared in Application Example 1 1 / 3 Mn 1 / 3 Fe 1 / 3 Characterization diagram of O2(NaNMF), where af is the element distribution diagram of SEM, g is the SEM morphology diagram, and h is the XRD diagram.
[0132] Depend on Fig.19 It can be seen that the NaNi prepared in Example 1 1 / 3 Mn1 / 3 Fe 1 / 3 O2 is an O3 type layered oxide cathode material.
[0133] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A sodium salt composition, characterized in that Including any five or more of sodium bis(trifluoromethanesulfonyl)imide, sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium fluoroborate, sodium nitrate, sodium perchlorate and sodium difluorophosphate.
2. The sodium salt composition according to claim 1, characterized in that The amount of each sodium salt in the sodium salt composition is the same.
3. A sodium ion battery electrolyte, characterized in that: comprising a sodium salt composition, an organic solvent and an additive; The sodium salt composition is the sodium salt composition according to claim 1 or 2; The solvation configuration of the sodium ion battery electrolyte is an aggregate with multipolar solvation shells; The concentration of the sodium salt composition in the sodium ion battery electrolyte is 0.5 to 0.8 mol / L; The volume percentage of the aggregate in the sodium ion battery electrolyte is 70-85%.
4. The sodium ion battery electrolyte according to claim 3, characterized in that The organic solvent includes one or more of tetrahydrofuran, ethylene glycol dimethyl ether and dioxolane.
5. The sodium ion battery electrolyte according to claim 3, characterized in that: The additive includes one or more of ethylene carbonate, vinylene carbonate, propylene sulfite and vinyl sulfate.
6. The sodium ion battery electrolyte according to claim 5, characterized in that The mass concentration of the additive in the sodium ion battery electrolyte is 3-5%.
7. Use of the sodium ion battery electrolyte according to any one of claims 3 to 6 in a sodium ion battery.
8. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The electrolyte is the sodium ion battery electrolyte according to any one of claims 3 to 6.
9. The sodium ion battery according to claim 8, characterized in that: The active material of the positive electrode includes layered oxides, Prussian blue compounds or polyanion compounds.
10. The sodium ion battery according to claim 8, characterized in that: The negative electrode includes hard carbon, sodium metal or sodium titanium phosphate.
Citation Information
Patent Citations
Electrolyte with high solvent-sodium salt ratio and sodium ion battery
CN113299976A
Sodium ion electrolyte matched with sodium vanadium phosphate positive electrode material and sodium metal negative electrode material and battery
CN116581388A
Non-aqueous high-entropy electrolyte and lithium ion battery
CN117254116A
Sodium-ion battery electrolyte as well as preparation method and application thereof
CN118659036A
High entropy liquid electrolytes for li-ion or na-ion batteries
WO2024123177A1
Cited By
Method for determining diffusion speed control steps of sodium ions in hard carbon and optimizing microstructure
CN121306293A